Bersama Santri, Ciptakan Pesantren Sehat dan Menyenangkan: Sebuah Program PKM Kreatif untuk Meningkatkan Kepedulian Kesehatan - Rahmat; Utama, Shella Febrita Puteri; Sastra, Jaka (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
Islamic boarding schools (pesantren) play a crucial role in shaping students' character and knowledge, but health issues in these environments often receive less attention. This community service program, titled “Bersama Santri, Ciptakan Pesantren Sehat dan Menyenangkan”, aims to increase health awareness in pesantren using a creative Photovoice approach. Through Participatory Action Research (PAR), students actively identified health problems and solutions within their boarding school. The program involved workshops, photography, and discussions, allowing students to document and reflect on their school's health conditions. Results showed significant improvements in clean and healthy living behavior (PHBS), with students' understanding of PHBS rising from 45% to 85%, handwashing habits increasing from 55% to 90%, and room cleanliness from 50% to 88%. This approach empowered students as agents of change, enhancing collective responsibility towards creating a healthier pesantren. The success of this program suggests potential replication in other pesantren to promote a healthier educational environment.